Evaluation of Aqueous and Ethanol Extracts of Alepidea amatymbica for Bio-active Constituents and Insecticidal Activity Against Tenebrio molitor - (:unkn) unknown (My University, 2025)
Alepidea amatymbica Eckl & Zeyh (Apiaceae) is a good source of bioactive compounds with folkloric use for the management of different ailments by the indigenous people of African descent. Despite the acclaimed traditional use of the plant, there is a dearth of scientific information on its use as a botanical insecticide. This study evaluated the impacts of aqueous and ethanol solvents on bio-active constituents yield of Alepidea amatymbica (A. amatymbica) and the insecticidal activities of the plant against Tenebrio molitor (T. molitor). The laboratory study was laid out in a completely randomized design of five treatments and a control. The treatment included; 1%, 0.75%, 0.50%, 0.25% and 0.125% concentrations of both aqueous and ethanol extracts of the plant. Larvae of T. molitor were subjected to the different concentration levels for mortality test. Data on the yield of bioactive compounds and insect mortality were subjected to analysis of variance, and mean differences were separated using Tukey’s Honestly Significant Test. Ethanol extraction of bioactive compounds gave significantly higher yield (14.48%) compared to the aqueous extraction (8.12%). Mortality of T. molitor was dependent upon the concentration levels of the aqueous and ethanol extracts of A. amatymbica. The larvae of T. molitor were significantly more susceptible to lower concentrations of ethanol extract than aqueous extract. However, both the aqueous and ethanol extracts of A. amatymbica proved to be toxic to the insect at relatively low concentrations between 0.125 and 0.50%. This study suggests that A. amatymbica could be explored for its insecticidal activity in the control of stored pests and other insect pests.
Keywords: African Research